Electronic assessment of clinical reasoning in clerkships: a mixed-methods comparison of long-menu key-feature problems with context-rich single best answer questions - Huwendiek, Sören; Hoffmann, Georg F.; Tönshoff, Burkhard (Medical teacher, 2017)
Background: It remains unclear which item format would best suit the assessment of clinical reasoning: context-rich single best answer questions (crSBAs) or key-feature problems (KFPs). This study compared KFPs and crSBAs with respect to students’ acceptance, their educational impact, and psychometric characteristics when used in a summative end-of-clinical-clerkship pediatric exam.Methods: Fifth-year medical students (n = 377) took a computer-based exam that included 6-9 KFPs and 9-20 crSBAs which assessed their clinical reasoning skills, in addition to an objective structured clinical exam (OSCE) that assessed their clinical skills. Each KFP consisted of a case vignette and three key features using a “long-menu” question format. We explored students’ perceptions of the KFPs and crSBAs in eight focus groups and analyzed statistical data of 11 exams.Results: Compared to crSBAs, KFPs were perceived as more realistic and difficult, providing a greater stimulus for the intense study of clinical reasoning, and were generally well accepted. The statistical analysis revealed no difference in difficulty, but KFPs resulted more reliable and efficient than crSBAs. The correlation between the two formats was high, while KFPs correlated more closely with the OSCE score.Conclusions: KFPs with long-menu exams seem to bring about a positive educational effect without psychometric drawbacks.
Gesehen am 10.10.2018